Development of Hemoglobin-based Oxygen Delivery System Using PEGylation - Cho, Hyemin; Kim, Kidong; Oh, Jaeeun; Park, Young Joon; Son, Sejin (Polymer (Korea), 2024)
Hemoglobin-based oxygen carriers can be used not only as blood substitutes but also as oxygen therapeutics for the treatment of hypoxemia, altitude sickness, carbon monoxide poisoning, chronic lung disease, and cancer. As COVID-19, population decline, and aging populations have raised concerns about the unreliability of the blood supply, hemoglobin-based oxygen carriers have become increasingly important in the development of artificial blood to replace donated blood. The strategy of conjugating polyethylene glycol (PEG) to hemoglobin has been used to mitigate the inher-ent problems of cell-free and substrate-free hemoglobin, such as toxicity, vasoconstriction, short half-life, and impairment of the immune system. In this review, we introduced the strategy of PEGylation as one of the methods for developing hemoglobin-based oxygen carriers.
Keywords: blood substitute; hemoglobin; hemoglobin-based oxygen carrier; oxygen therapeutics; PEGylation; polyethylene glycol